Selection and validation of reference genes for normalization of quantitative real-time reverse transcription PCR analysis in Poria cocos (Schw.) Wolf (Fuling). Issue 1 (December 2016) - Zhang, Xin; Xu, Zhi-Chao; Xu, Jiang; Ji, Ai-Jia; Luo, Hong-Mei; Song, Jing-Yuan; Sun, Chao; Hu, Yuan-Lei; Chen, Shi-Lin
Abstract Background Quantitative real-time reverse transcription PCR (qRT-PCR) requires a stable internal control to avoid misinterpretation of data or errors for gene expression normalization. However, there are still no validated reference genes for stable internal control inPoria cocos (Schw.) Wolf (Fuling ). This study aims to validate the reference genes ofP. cocos . Methods This study firstly collected the 14 candidate reference genes by BLASTP from the genome ofP. cocos for qRT-PCR analysis to determine the expression levels of 14 housekeeping genes (GAPDH, MAPK, β -Act, RPB2, RPB1 -1, RPB1 -2, his3 -1, his3 -2, APT, SAMDC, RP, β -Tub, EIF, andCYP ) under different temperatures and in response to different plant hormones (indole-3-acetic acid, abscisic acid, 6-benzylaminopurine, methyl jasmonate, and gibberellic acid), and the threshold cycle (Ct ) values. The results were analyzed by four programs (i.e., geNorm, NormFinder, BestKeeper, and RefFinder) for evaluating the candidate reference genes. Results SAMDC, his3 -2, RP, RPB2, andhis3 -1 were recommended as reference genes for treatingP. cocos with indole-3-acetic acid, abscisic acid, 6-benzylaminopurine, methyl jasmonate, and gibberellic acid, respectively. Under different temperaturesRPB2 was the most stable reference gene.CYP was the most stable gene for all 90 samples by RefFinder. Conclusion SAMDC, his3 -2, RP, RPB2, andhis3 -1 were evaluated to be suitable reference genes forP. cocos following different treatments.RPB2 was the most stable reference gene under different temperatures andCYP was the most stable gene in the mycelia under all six evaluated conditions.